2021
DOI: 10.26444/aaem/133100
|View full text |Cite
|
Sign up to set email alerts
|

Demographic analysis of difficulties related to remote education in Poland from the perspective of adolescents during the COVID-19 pandemic

Abstract: Introduction and objective. Due to the COVID-19 pandemic all schools in Poland were closed and obliged to conduct lessons remotely. The aim of the study is to present the demographic analysis of difficulties with remote learning, as perceived by students during coronavirus pandemic in Poland. Materials and method. In April 2020, a nationwide online survey was conducted among adolescents aged 11-18 (N=2408). Quantitative and qualitative data were used. Teenagers were asked about the problems connected with remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 21 publications
1
49
0
1
Order By: Relevance
“…Five studies found no significant difference in the experience of students based on gender: in Jordan (Al Salman et al, 2021), Italy (Ferraro et al, 2020;Pirrone et al, 2021), Poland (Korzycka et al, 2021), and Vietnam (Tran et al, 2020). Although in Korzycka et al's (2021) study, girls were significantly more likely than boys to have an issue with the requirements of home schooling (59.6% vs. 53.2%; p=0.001).…”
Section: Gender Implicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Five studies found no significant difference in the experience of students based on gender: in Jordan (Al Salman et al, 2021), Italy (Ferraro et al, 2020;Pirrone et al, 2021), Poland (Korzycka et al, 2021), and Vietnam (Tran et al, 2020). Although in Korzycka et al's (2021) study, girls were significantly more likely than boys to have an issue with the requirements of home schooling (59.6% vs. 53.2%; p=0.001).…”
Section: Gender Implicationsmentioning
confidence: 94%
“…The studies were also categorised according to sample size (see Appendix I). 18.5% of studies had more than 400 participants, with three European studies having over 2,000, from Slovakia (Velichová et al, 2020), Poland (Korzycka et al, 2021), and Austria (Pelikan et al, 2021). 33% of studies (n = 27) had between one and 25 participants, which represents a higher percentage of smaller scale studies than in higher education research (16%, .…”
Section: Figure 5 Year Levels Representedmentioning
confidence: 97%
“…and "Would your parent help you if you had a problem?" The response categories ranged from never (1) to always (5).…”
Section: Methodsmentioning
confidence: 99%
“…One of many early preventive measures taken against the spread of the virus was the government's decision to close all schools (11 March 2020). Subsequently, starting from March 2020, remote education was implemented and developed throughout 2020 and 2021 [5]. Psychological burdens, social isolation and loneliness have been among the many problems emphasized by Polish adolescents (aged [11][12][13][14][15][16][17][18], which have been also experienced due to online education [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation